1999
DOI: 10.1021/ma981927a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Growth of Polyelectrolyte Multilayers

Abstract: The dependence of polyelectrolyte multilayer thickness on salt concentration, salt type, solvent quality, deposition time, and polymer concentration is evaluated. Polymers are deposited on spinning silicon wafers. For the strong polycation/polyanion pair studied, film thickness is approximately proportional to the number of layers and the salt concentration. The irreversibility of overall molecule adsorption is indicated by the lack of exchange of surface (radiolabeled) for solution polymer. The hydrophobic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
1,075
7
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 913 publications
(1,135 citation statements)
references
References 57 publications
47
1,075
7
6
Order By: Relevance
“…In contrast, PSS, a strong anionic polyelectrolyte, possesses a number of negative charges along its backbone chain. Due to their strong ionic charges, both PDADMAC and PSS have been used as the polyelectrolytes for PEM preparation [22][23][24][25] . Since the hydrophobic ring structure of PDADMAC polycations is stiff and consequently difficult to rotate both in water and in air, the outer layer containing the quaternary ammonium end groups will stay hydrophilic both in water and in air.…”
Section: Differentiation Of Mc3t3-e1 On Poly(4-styrenesulfonic Acid-cmentioning
confidence: 99%
“…In contrast, PSS, a strong anionic polyelectrolyte, possesses a number of negative charges along its backbone chain. Due to their strong ionic charges, both PDADMAC and PSS have been used as the polyelectrolytes for PEM preparation [22][23][24][25] . Since the hydrophobic ring structure of PDADMAC polycations is stiff and consequently difficult to rotate both in water and in air, the outer layer containing the quaternary ammonium end groups will stay hydrophilic both in water and in air.…”
Section: Differentiation Of Mc3t3-e1 On Poly(4-styrenesulfonic Acid-cmentioning
confidence: 99%
“…5 Using techniques such as X-ray and neutron reflectivity, it has been found that binary films of polyelectrolytes resemble polyelectrolyte complexes (PEC), particularly for thick films, as a result of the high amount of interpenetration of the layers. [6][7][8][9] While it is widely accepted that adsorbed water could have a large influence on the behavior of the film, neutron reflectivity is unable to observe it directly, although it has been incorporated into models for the data. 6 Thus, only a few studies so far have been able to probe the behavior of water in the films, [10][11][12] and none have probed it directly in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Because the degree of charge dissociation in polyelectrolytes is dependent on the types of ion-pairs, the physical properties of polyelectrolyte hydrogels such as conductivity, elasticity and swelling ratio are affected by counterions as well as external stimuli. [14][15][16][17] Recently, there have been increasing research efforts of combining hydrogels with other functional materials to extend their potential applications. For example, the photonic crystals comprising hydrogels exhibit unique tunable photonic band gaps in response to the various stimuli including temperature, pH, ionic strength, solvent compositions and electric fi eld.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%